2017
DOI: 10.1002/rob.21732
|View full text |Cite
|
Sign up to set email alerts
|

Autonomous aerial navigation using monocular visual‐inertial fusion

Abstract: Autonomous micro aerial vehicles (MAVs) have cost and mobility benefits, making them ideal robotic platforms for applications including aerial photography, surveillance, and search and rescue. As the platform scales down, MAVs become more capable of operating in confined environments, but it also introduces significant size and payload constraints. A monocular visual-inertial navigation system (VINS), consisting only of an inertial measurement unit (IMU) and a camera, becomes the most suitable sensor suite in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
176
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 204 publications
(176 citation statements)
references
References 58 publications
0
176
0
Order By: Relevance
“…Such representations can be sparse [184], semidense [185], or fully dense [186]. While dense representations can be directly used for autonomous navigation [186] or geographical reference, sparse representations are often only used for state estimation [187] or collaborative control of robotic agents. Due to the fact that the environment is often only partially known or even totally unknown, mapping tasks are often coupled with localization (pose estimation) issues, which turn them into the classic simultaneous localization and mapping (SLAM) problem.…”
Section: Cooperative Aerial Mappingmentioning
confidence: 99%
“…Such representations can be sparse [184], semidense [185], or fully dense [186]. While dense representations can be directly used for autonomous navigation [186] or geographical reference, sparse representations are often only used for state estimation [187] or collaborative control of robotic agents. Due to the fact that the environment is often only partially known or even totally unknown, mapping tasks are often coupled with localization (pose estimation) issues, which turn them into the classic simultaneous localization and mapping (SLAM) problem.…”
Section: Cooperative Aerial Mappingmentioning
confidence: 99%
“…Recent work has shown that obstacle detection for reactive collision avoidance is possible at high speeds on a CPU (68) running onboard a fixed-wing aircraft traveling at up to 14 m/s. However, maintaining a complete map for longer-range planning is computationally expensive, and as a result, most mapping algorithms have been executed using either offboard resources (50) or onboard specialized hardware, such as GPUs (53) or field-programmable gate arrays (69). These mapping algorithms can be combined with trajectory-generation methods to enable autonomous navigation through cluttered environments (49,53,68).…”
Section: State Estimation and Perceptionmentioning
confidence: 99%
“…Many works have successfully demonstrated autonomous navigation in unknown workspaces using completely onboard mapping, estimation, planning, and control pipelines (53,66,85,86,90) (49,85), which uses a stereo camera and IMU for estimation and a laser sensor for mapping, can reach speeds of 7 m/s. Figure 5 illustrates identified safe trajectories from a single start position to multiple goals throughout a space.…”
Section: Applications For Agile High-speed Flightmentioning
confidence: 99%
“…The dimensions of a small platform also limit its ability to carry stereo or multicamera systems due to insufficient baseline length. As the platform becomes smaller, a monocular visualinertial navigation system (VINS), consisting of only a low-cost inertial measurement unit (IMU) and a camera, becomes the only viable sensor suite allowing autonomous flights with sufficient environmental awareness [4].…”
Section: Introductionmentioning
confidence: 99%
“…Recent research on VINS for MAVs have yielded a number of significant results [1][2][3][4]11]. Most of these existing approach can be classified into filter-based and optimization-based systems.…”
Section: Introductionmentioning
confidence: 99%